Red Vienna. 1919–1934 - Glebova, Natalya; Klamer, Michael (project baikal, 2021)
The political events and global socio-economic reforms carried out by social democrats in the early 20th century, expansion of the capital of Austria and the inflow of the working class caused the building of a “garden city” with rich infrastructure, parks and available and comfortable dwelling. The skills of advanced Austrian architects, ideological meaning together with economic forces, spatial concept and socialist slogans gave birth to a new architectural identity.
Keywords: Social Democratic Party; social municipal housing; Gemeindebauten; architectural identity; Otto Wagner school; Austrian architects